Transforaminal Insertion of a Thermocouple on the Posterior Vertebral Wall Combined with Hydrodissection during Lumbar Spinal Radiofrequency Ablation - Lecigne, R. (AJNR Am J Neuroradiol, 2019)
The purpose of the present article is to describe the technique of transforaminal insertion of an ultrathin thermosensor in the anterior epidural space in 13 patients treated by radiofrequency ablation. The mean time taken to position the thermosensor was 10.6 minutes (range, 5–38 minutes). Technical success was 93% (correct positioning in 13/14 levels). Additional hydrodissection was performed through the same access in 11 cases. No postoperative neural deficit was elicited in any of the cases.